Single Mom: Pemenuhan Fungsi Afeksi dan Ekonomi pada Anak - Rositah, Rositah; Hidayati, Dewi Ayu (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This research aims to analyze the fulfillment of economic and affectional functions for children carried out by single mothers who work as small traders in the Tamin market, Bandar Lampung city. This research is important to carry out so that single mothers continue to provide affection and economic functions even though they come from incomplete families. This research was carried out using a qualitative approach to analyze in depth the phenomena related to single mothers as well as the fulfillment of the affection and economic functions carried out by single mothers for his children. The research informants were 5 people who were single mothers who worked as small traders. Data collection techniques include observation, in-depth interviews and documentation. Data analysis was carried out in stages of reduction, data presentation and data verification. The research results show that the economic function carried out by single mothers who work as small traders is by doing side jobs, extending working hours, asking family members for help, borrowing, saving money and taking advantage of assistance from the government. Meanwhile, the affection function is carried out by spending time, controlling relationships, providing religious knowledge, giving advice